The Impact of Artificial Intelligenceon Taxpayer Compliance - Suryadi, Ibnu; Purba, Rebeka Meidiana; Tampubolon, Amy Septrina; Ersanti, Ersanti; Ramadhon, Rosiana (Sharia Journal and Education Center Publishing, 2026)
The rapid evolution of digital technology has ushered in a new era of tax administration, characterized by the integration of Artificial Intelligence (AI). This research investigates the impact of AI implementation on taxpayer compliance, examining both the technical efficiency of tax authorities and the behavioral shifts among taxpayers. Using a comprehensive literature review and a conceptual framework based on the Technology Acceptance Model (TAM) and Deterrence Theory, this study analyzes how AI-driven tools—such as automated auditing, predictive analytics for fraud detection, and AI-powered chatbots—influence voluntary and enforced compliance. The findings suggest that AI significantly enhances compliance by reducing the